2019
DOI: 10.1139/cjz-2018-0157
|View full text |Cite
|
Sign up to set email alerts
|

The effects of repeat acute thermal stress on the critical thermal maximum (CTmax) and physiology of juvenile shortnose sturgeon (Acipenser brevirostrum)

Abstract: The shortnose sturgeon (Acipenser brevirostrum Lesueur, 1818) is a species of special concern in Canada, but little is known about their thermal biology. Information on the upper thermal tolerance of shortnose sturgeon becomes valuable for predicting future survival particularly with climate change and improving species management. Using a modified critical thermal maximum (CTmax) methodology, the objective is to determine whether previous thermal stress affects the thermal tolerance of juvenile shortnose stur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
1
10
0
Order By: Relevance
“…Our findings for shortnose sturgeon CT max values are similar to previously published data (Bard & Kieffer, 2019; Spear & Kieffer, 2016; Zhang et al, 2017; Zhang & Kieffer, 2014; Ziegeweid et al, 2008), and further confirms the relationship between acclimation temperature and CT max across fish species, including shortnose sturgeon (Chatterjee et al, 2004; Currie et al, 1998; Das et al, 2004, 2005; Dülger et al, 2012; Ford & Beitinger, 2005; Martìnez et al, 2016; McKenzie et al, 2021; Peng et al, 2014; Zhang & Kieffer, 2014; Ziegeweid et al, 2008). In the current study, we found that the acclimation response ratio was 0.81 in shortnose sturgeon, which indicates that for each 1°C in environmental temperature, the CT max of shortnose sturgeon increased by 0.81°C.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings for shortnose sturgeon CT max values are similar to previously published data (Bard & Kieffer, 2019; Spear & Kieffer, 2016; Zhang et al, 2017; Zhang & Kieffer, 2014; Ziegeweid et al, 2008), and further confirms the relationship between acclimation temperature and CT max across fish species, including shortnose sturgeon (Chatterjee et al, 2004; Currie et al, 1998; Das et al, 2004, 2005; Dülger et al, 2012; Ford & Beitinger, 2005; Martìnez et al, 2016; McKenzie et al, 2021; Peng et al, 2014; Zhang & Kieffer, 2014; Ziegeweid et al, 2008). In the current study, we found that the acclimation response ratio was 0.81 in shortnose sturgeon, which indicates that for each 1°C in environmental temperature, the CT max of shortnose sturgeon increased by 0.81°C.…”
Section: Discussionsupporting
confidence: 92%
“…The arena was then covered with a fitted piece of plexiglass to prevent the fish from escaping. The fish was held in the test arena for 1 h to recover from handling stress (Bard & Kieffer, 2019; Spear & Kieffer, 2016; Zhang & Kieffer, 2014). Then individual fish were subjected to a thermal stress (i.e., heating or cooling) (see Table 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cortisol responses during and after an acute temperature rise have been described for multiple species (Table 1), with only a few exceptions [e.g., LeBlanc et al (2012) and Chadwick et al (2015)]. Secondary stress responses are also observed on acute temperature increase; glucose and lactate generally rise during acute thermal challenge, along with alterations in blood osmolality and other haematological variables (Bard & Kieffer, 2019;Dengiz Balta et al, 2017). In addition, inhibitory effects on the fish immune system may be observed (Dengiz Balta et al, 2017).…”
Section: Acute Warming As An Acute Stressor For Fishesmentioning
confidence: 99%
“…(2015)]. Secondary stress responses are also observed on acute temperature increase; glucose and lactate generally rise during acute thermal challenge, along with alterations in blood osmolality and other haematological variables (Bard & Kieffer, 2019; Dengiz Balta et al ., 2017). In addition, inhibitory effects on the fish immune system may be observed (Dengiz Balta et al ., 2017).…”
Section: Global Warming and Fish Stress Physiologymentioning
confidence: 99%